2019
DOI: 10.4149/neo_2018_180302n146
|View full text |Cite
|
Sign up to set email alerts
|

Tumor suppressor let-7a inhibits breast cancer cell proliferation, migration and invasion by targeting MAGE-A1

Abstract: Let-7 was one of the earliest discovered miRNAs and while it reportedly acts as a tumor suppressor in various solid tumors, its function in breast cancer has not been fully studied. Therefore, we examined let-7a and MAGE-A1 expression in breast tissues by qRT-PCR and found that let-7a expression significantly correlates with larger tumor size, higher histological grade (p<0.05) and is significantly lower in patients with Her-2-positive cancers and Ki-67 >14% (p=0.028 and p=0.023). MAGE-A1 expression incidence … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 28 publications
0
10
0
1
Order By: Relevance
“…It has been validated as RG in lymph node tissues 57 . Notably, let-7a is downregulated in breast cancer, prostate cancer, cervical cancer [58][59][60][61] … So far, there is no evidence in the literature of the implication of miR-191-5p, miR-34b-3p and let-7a-5p in the physiology of MSCs. To validate the selected RGs, the relative expression of miR-21-5p was measured by RT-qPCR.…”
Section: Discussionmentioning
confidence: 99%
“…It has been validated as RG in lymph node tissues 57 . Notably, let-7a is downregulated in breast cancer, prostate cancer, cervical cancer [58][59][60][61] … So far, there is no evidence in the literature of the implication of miR-191-5p, miR-34b-3p and let-7a-5p in the physiology of MSCs. To validate the selected RGs, the relative expression of miR-21-5p was measured by RT-qPCR.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that MAGE-A gene products are involved in ubiquitination, proliferation, and apoptosis [31,41,[53][54][55]. The relationship between MAGE-A proteins and ubiquitination is well known; for example, MAGEA3 and MAGEA6 form an E3 ubiquitin ligase complex with TRIM28, which participates in the survival of cancer cells by degrading AMPKa1 [31,55].…”
Section: Discussionmentioning
confidence: 99%
“…Intriguingly, both Let-7a and miR-26a were found downregulated in several human cancer types, acting as tumor-suppressor miRNAs [36][37][38][39][40]. Moreover, these miRNAs inhibited cell proliferation and invasiveness of malignant melanoma derived-cell lines, suggesting that miR-26a and Let-7a may represent novel therapies for melanoma [41].…”
Section: Discussionmentioning
confidence: 99%